Financial Dollarization, (De)Dollarization and The Turkish Experience - Gokhan Yilmaz (Turkish Economic Association, 2005)
This paper briefly discusses the causes and consequences of financial dollarization with special reference to the recent Turkish experience. Most developing countries have a limited,unofficial form of dollarization, which makes them vulnerable to external shocks through currency mismatches. Financial dollarization can limit the scope of macroeconomic policies and cause fear of floating. Consequently, dedollarization policies are now shifting from a generally passive stance learning to live with it type approach to a more active stance such as carrot and stick approach. This paper also presents a composite financial dollarization index for Turkey along with a brief discussion of corporate sector debt dollarization. The recent Turkish experience towards endogenous dedollarization appears to be consistent with the view that dedollarization can also be viewed as a side effect of prudent fiscal and monetary policies. Although the dollarization composite index is on a decreasing trend, it is however still high. Therefore, an active dedollarization strategy associated with a sound macroeconomic policy stance should be considered to support the implementation of a Full Fledged Inflation Targeting Regime in the near future.
Keywords: 330; Financial Dollarization; Dedollarization; Turkey